Alat Press Hidraulik Pada Industri Rumah Tangga Pembuatan Tahu Jawa Di Dusun Karang Kelok, Mataram - Nurchayati Nurchayati; Hendry Sakke Tira; Yesung Allo Padang; Rudy Sutanto; Suteja Suteja (Jurusan Teknik Mesin FT Universitas Mataram, 2023)
In Karang Kelok hamlet, West Monjok, Mataram, there are currently 2 Home Industries (IRT) that make tofu and are known as Javanese tofu. Because the texture is different from the Lombok tofu in general, this tofu is in great demand by the wider community. So the demand in every day is very much. One of them belongs to Tin's mother. This IRT is able to absorb 3 workers. Every day able to spend 60 kg of soybeans. In producing the tofu, this IRT still uses the traditional method, especially when pressing the tofu is still done by overlapping 1-3 pieces of stone with different weights. Pressing in this way has weaknesses, including security and work safety issues. This condition is also one of the obstacles to be able to produce more tofu products. This pressing is done one by one and in a row, so it also takes up a wider area. Based on these problems, it is necessary to plan and manufacture hydraulic system tofu pressing tools so that the resulting product increases. The purpose of this service is to get a smaller time and area for pressing in the tofu-making process. The method used is to socialize the use of a hydraulic system tofu press. The results obtained are that this tofu press tool can shorten the average pressing time of 4 minutes and reduce the working area of pressing from 3 meters to 1 meter. And it can also reduce the risk of work accidents due to the fall of the crushing stone.